Activity of antifungal drugs and Brazilian red and green propolis extracted with different methodologies against oral isolates of Candida spp. - Ana Rita Sokolonski; Maísa Santos Fonseca; Bruna Aparecida Souza Machado; Kathleen Ramos Deegan; Roberto Paulo Correia Araújo; Marcelo Andrés Umsza-Guez; Roberto Meyer; Ricardo W. Portela (BMC, 2021)
Abstract Background Oral candidiasis is an opportunistic disease caused by fungi of the Candida genus. The occurrence of Candida spp. resistance to the commercial antifungal drugs points to the search for alternative treatments. Propolis has been successfully used in the treatment of infectious diseases for centuries. It has been proposed that an ultrasound pretreatment in the propolis extraction protocol can enhance the concentrations of molecules with antimicrobial activities in the final extract. Thus, this study aimed to compare the antifungal activity against oral Candida spp. isolates of green and red propolis extracts submitted or not to an ultrasound pretreatment before the extraction procedure. Methods Candida spp. were isolated from denture stomatitis lesions and identified by sequencing. Oral Candida spp. isolates and reference strains were submitted to broth microdilution assays using commercial antifungals and Brazilian green and red propolis extracts submitted or not to an ultrasound pretreatment. Minimal Inhibitory Concentrations (MIC) and Minimal Fungicide Concentrations (MFC) were determined and biofilm formation interference was evaluated for resistant isolates. Results C. albicans, Candida tropicalis and Candida dubliniensis were isolated from denture stomatitis lesions. Growth inhibition was observed in all Candida isolates incubated with all green and red propolis extracts. At lower doses, red propolis extracts presented significant antifungal activity. The ultrasound pretreatment did not promote an increase in the antifungal activity of green or red propolis. Three isolates, which were highly resistant to fluconazole and itraconazole, were susceptible to low doses of red propolis extracts. These same three specimens had their biofilm formation inhibted by red propolis ethanolic extract. Conclusions Thus, red propolis can be faced as a promising natural product to be used in the auxiliary antifungal therapy of denture stomatitis.